The Transit-Oriented Development (TOD) Improvement Towards a Sustainable Development - Saidan Khaderi, Shamsida; Bakeri, Nur Nadzirah; Abd Shukor, Ani Saifuza (International Journal of Sustainable Construction Engineering and Technology, 2021)
Transit-Oriented Development (TOD) is gaining popularity as a tool to achieve sustainable development. It consists of a mixed-use development, which can cater to urban sprawl, road traffic congestion and an increase in carbon gas emission. There are efforts and incentives by the Malaysian policies related to TOD constructed under the Eleventh Malaysian Plan (RMK-11) to encourage public transportation, walking, and cycling as an alternative to the main modes. However, the efforts seem in vain as the public are not concerned regarding this issue. This study examined TOD's implementation towards sustainable community with the following objectives: to determine the criteria and concept of TOD, investigate the issues and challenges in implementing TOD towards sustainable development, and recommend TOD improvement towards a sustainable development. The scope of this study is to identify the TOD implementation around Subang Jaya station towards sustainable development. A mixed-method of qualitative and quantitative research is used in a semi-structured interview, questionnaire distribution, observation, and document analysis. The quantitative data collected was analyzed using Statistical Package for Social Science (SPSS) 22, while the qualitative data was analyzed using content analysis. The results show that the implementation of TOD still immature and in the developing phase. The top three criteria were identified; reduce private vehicle and road traffic congestion, reduce pollution and carbon emission, and connectivity to other spaces or area. Three significant issues and challenges identified; a limited number of park-and-ride facilities, housing price around transit station and quality service of the public transportation served by related agencies. A workable recommendation for TOD improvement towards a sustainable community developed after industry practitioners tested it. These suggestions and guidance can help industry players in making sound decisions when undertaking TOD projects.